SI PARASIT LAJANG: POTRET PEREMPUAN METROPOLITAN - Saksono Prijanto (Balai Bahasa Provinsi Riau, 2014)
The presence of novel Saman by Ayu Utami surprised the world of Indonesian literature. Response to readers and literary critics of Saman diverse, both those in favor, cursing and not be silent. Ayu Utami is a productive female novelist because she continuously has been published novel Saman and Larung (dualogy), Serial Numbers Fu (Manjali and Cakrabirawa and Lalita), and the trilogy (Parasit Lajang, Enrico Love Story, Parasit Lajang—Ex Parasit Lajang). Ayu Utami‟s achievement in writing, among others are